An injectable mitochondria-targeted nanodrug loaded-hydrogel for restoring mitochondrial function and hierarchically attenuating oxidative stress to reduce myocardial ischemia-reperfusion injury. (August 2022) - Zhang, Xiaoping; Sun, Yage; Yang, Rong; Liu, Bo; Liu, Yang; Yang, Jianhai; Liu, Wenguang
Abstract: Timely reperfusion is the common treatment for myocardial infarction. However, ischemia-reperfusion (I/R) therapy can lead to oxidative stress and mitochondrial dysfunction that further aggravate myocardial injury, and no effective therapy is currently available for alleviating myocardial I/R injury. Herein, we engineer a mitochondria-targeted Szeto-Schiller (SS31) peptide modified-amphiphilic polymer (PTPS) that self-assembles into nanomicelles (PTPSCs) for loading cyclosporine A (CsA). The PTPSCs are then encapsulated into a pH/ROS dual responsive injectable hydrogel crosslinked with reversible imine and boronic ester bonds. The loaded PTPSCs are controllably delivered from the hydrogel matrix in response to the low pH and high ROS microenvironment of the I/R heart, thus realizing reconstruction of mitochondrial function and unprecedented hierarchical attenuation of oxidative stress. The boronic ester in the hydrogel consumes the ROS in cardiac microenvironment, and the mitochondria-targeted delivery of CsA is revealed to inhibit mitochondria-mediated apoptosis signaling pathway to prevent cardiomyocyte apoptosis, meanwhile attenuating the mitochondrial ROS output to reduce the level of cytosolic ROS. Additionally, SS31 can also serve as an antioxidant to consume ROS in the mitochondria. In rat model of myocardial I/R injury with administration of this injectable hydrogel, the targeted release of PTPSCs efficiently restores mitochondrial and cardiac function.